Typification of the name Ferulago galbanifera (Apiaceae) and its priority over the name F. campestris - Lyskov, Dmitry (Phytotaxa, 2020)
Both names Ferulago campestris (Besser 1822: 44) Grecescu (1898: 252) and F. galbanifera (Miller 1768: no pagination) Koch (1835: 302) are used now simultaneously for one taxon which is widely distributed from southwestern Europe to southwestern Russia. On the one hand, the name F. campestris is used in such sources as Flora of URSS (Schischkin 1951), Flora Europaea (Cannon in Tutin 1968), a monographic study of the genus Ferulago (Bernardi 1979), The Euro Med treatment of Apiaceae (Hand 2011), GBIF database (GIBF 2020), and numerous articles. On the other hand, F. galbanifera is mentioned in Flora of Turkey (Peşmen in Davis 1972), Plantae Vasculares URSS (Czerepanov 1981), Umbelliferae of Russia (Pimenov & Ostroumova 2012), The Plant List (2013 onwards), and numerous articles. This name is also mentioned as the type of Ferulago subgen. Galbanifera Pimenov & Tomkovich in Tomkovich & Pimenov (1987: 968).